Nanomaterial‐wrapped dsCYP15C1, a potential RNAi‐based strategy for pest control against Chilo suppressalis. Issue 7 (24th February 2020) - Sun, Yajie; Wang, Peipei; Abouzaid, Mostafa; Zhou, Hao; Liu, Hui; Yang, Pan; Lin, Yongjun; Hull, J Joe; Ma, Weihua
Abstract: BACKGROUND: Although the utility of double‐stranded RNA (dsRNA)‐mediated knockdown as an environmentally friendly pest management strategy has gained traction in recent years, its overall efficacy has been limited by poor stability and limited cellular uptake. Encapsulation of dsRNAs with various nanomaterials, however, has shown promise in overcoming these limitations. This study sought to investigate the biological efficacy of an oral dsRNA nanomaterial mixture targeting the CYP15C1 gene product in the economically important rice pest, Chilo suppressalis . RESULTS: A putative CYP15C1 ortholog was cloned from C. suppressalis midguts. The transcript is downregulated in fifth‐instar larvae and is most highly expressed in heads. RNA interference (RNAi)‐mediated knockdown of CsCYP15C1 was associated with significantly increased mortality. More importantly, feeding a dsRNA–nanomaterial mixture significantly increased larval mortality compared with feeding dsRNA alone. CONCLUSION: A critical role for CsCYP15C1 function in molting is supported by sequence similarity with known juvenile hormone epoxidases, its expression profile, and abnormal molting phenotypes associated with RNA‐mediated knockdown. CsCYP15C1 is thus a prime target for controlling C. suppressalis . Furthermore, RNAi‐mediated characterization of candidate gene function can be enhanced by incorporating an enveloping nanomaterial. © 2020 Society of Chemical Industry Abstract : This study sought to investigate the biological efficacy of an oral dsRNA–nanomaterial mixture targeting the CYP15C1 gene product in the economically important rice pest, Chilo suppressalis .